2014
DOI: 10.1111/brv.12155
|View full text |Cite
|
Sign up to set email alerts
|

Larval dispersal and movement patterns of coral reef fishes, and implications for marine reserve network design

Abstract: Well-designed and effectively managed networks of marine reserves can be effective tools for both fisheries management and biodiversity conservation. Connectivity, the demographic linking of local populations through the dispersal of individuals as larvae, juveniles or adults, is a key ecological factor to consider in marine reserve design, since it has important implications for the persistence of metapopulations and their recovery from disturbance. For marine reserves to protect biodiversity and enhance popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
424
2
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 339 publications
(439 citation statements)
references
References 234 publications
(244 reference statements)
10
424
2
3
Order By: Relevance
“…Populations connected by surface-advected coral propagules also have genetic structure shaped by oceanography (Baums et al 2006, Wood et al 2016. A review of dispersal focused on reef fish (with a similar length pelagic dispersal phase as conch) suggested that scales of protection should be equivalent to double the dispersal potential (Green et al 2015). However, the continuing decline we observed in the ECLSP suggests that in some areas source and sink dynamics outweigh generalizations and can cause inefficacy (D'Agostini et al 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Populations connected by surface-advected coral propagules also have genetic structure shaped by oceanography (Baums et al 2006, Wood et al 2016. A review of dispersal focused on reef fish (with a similar length pelagic dispersal phase as conch) suggested that scales of protection should be equivalent to double the dispersal potential (Green et al 2015). However, the continuing decline we observed in the ECLSP suggests that in some areas source and sink dynamics outweigh generalizations and can cause inefficacy (D'Agostini et al 2015).…”
Section: Discussionmentioning
confidence: 93%
“…While even isolated populations with low larval supply may be replenished, given enough time (Gilmour et al 2013), it can be argued that connectivity likely dominates habitat quality as the primary mechanism of efficacy for self-sustaining MPAs in some systems (Pinsky et al 2012, White et al 2014, D'Agostini et al 2015. Overall, a review of movement patterns suggests that the most effective MPAs encompass both adult and larval dispersal while also containing the appropriate mix of key habitats for any given species (Green et al 2015). If a species has limited movement as an adult, the ecological efficacy of a MPA in protecting a population should depend on both the habitats protected and the supply of larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Planning considerations such as MPA size, spacing, and location can also influence the achievement of ecological objectives (Green et al 2014). However, there are critical trade-offs in planning between achieving compliance and achieving ecological objectives.…”
Section: Discussionmentioning
confidence: 99%
“…1). Ecological considerations for planning MPAs commonly suggest that large, no-take MPAs are preferable to smaller ones because they can, for instance, encompass more habitats and highly mobile species, and offer higher levels of protection (Edgar et al 2014, Green et al 2014. However, larger MPAs can be harder to manage, and excluding fishing from coastal MPAs in developing countries is likely to create friction with fishing communities (Ban et al 2011); hence, compliance and resultant ecological health are likely to weaken.…”
Section: Discussionmentioning
confidence: 99%
“…This was accounted for in selections of control sites and will also be incorporated in post-hoc analyses. We identified an appropriate buffer of 5 km to account for the home range of most of the species of interest [47]. While most of the control sites are located at distances more than 10 km from MPA boundaries, four non-MPA sites are located less than 5 km from the boundaries of MPAs.…”
Section: Mpamentioning
confidence: 99%